Utilizing Moringa Leaves to Turn a Valuable Product in Kesemen Ngoro Village, Mojokerto - Masruchan (Future Tecno-Science Publisher, 2025)
Moringa leaves have excellent potential to complement the nutritional needs of the human body. Moringa leaves can be used as processed products with high nutritional value and higheconomic value. Opportunities to develop in this field are also wide open because this sector has not been fully utilized by society. Moringa can be used as one of the mainstay commodities to be developed better. Therefore, we choose moringa as the object of research to be used asa an article. In this article discusses the wise use of moringa leaves. The purpose of this activity is to increase public insight and knowledge about plants and their benefits, as well as increase public knowledge about processing and various moringa-bassed processed products. The method of implementing this activity is carried out directly through community socialization regarding the benefits and processing of Moringa leaves in Kesemen Ngoro Mojokerto.